Iron metabolism in oligodendrocytes and astrocytes: friend or foe? - Pasquini, Juana Maria (2021)
Recent reports show that astrocytes (AST) are able to create a permissive environment for remyelination through their action on oligodendrocyte (OLG) precursor migration, proliferation, and differentiation. When disrupted, iron homeostasis negatively impacts OLG differentiation and impairs myelination. We demonstrate that iron deficiency (ID) affects not only OLG maturation but also AST. Using gestational iron deprivation, we studied OLG requirements for their progression to a mature myelinating state and energy metabolism in primary cultures of OLG and AST from newly born control and ID pups. In particular, oxygen consumption and extracellular acidification rates were measured using a Seahorse extracellular flux analyzer. Both ID AST and OLG exhibited decreased spare respiratory capacity, which indicates that maternal ID effectively induces mitochondrial dysfunction. Absence of glycogen granules was observed in ID AST and an increase in ROS production was detected in ID OLG. Mitochondrial fission was increased in ID AST, while fusion was prevalent in ID OLG. Electron microscopy also showed abnormal cristae in ID mitochondria in OLG as well as in AST. These findings further prove that the regulation of cell metabolism may impact cell fate decisions and maturation. An additional model of ID was developed by knocking down the divalent metal transporter 1 (DMT1), a multi-metal transporter with a primary role in iron transport and present in AST and OLG. OLG maturation was compromised in primary OPC cultures treated with conditioned medium from DMT1-silenced AST, which suggests that molecules secreted by AST may be affected.